Translation, validity and reliability of a Malay version of the toddler sensory profile 2 - Png, JieYi; Kadar, Masne; Wan Yunus, Farahiyah; Yang, Wai Wai; Ahmad Rusli, Yasmin; Abdul Khaiyom, Jamilah Hanum (Taylor & Francis, 2022)
Sensory processing is an essential development in toddlers. A common sensory measurement tool used by Malaysian occupational therapists is Toddler Sensory Profile 2 (TSP 2). However, the Malay version has yet to be translated and validated for TSP 2 among toddlers in Malaysia. The translation and validation are a necessary process due to cross-cultural differences between English-speaking and Malay-speaking communities. The main aim of this study is to translate and identify the validity and reliability of the Toddler Sensory Profile 2- Malay version (TSP 2-M). This study involved four phases: (I) Forward and backward translations; (II) Content validation by an expert panel; (Ill) Pre-testing through cognitive interviews; (IV) Internal consistency of psychometric measure through a pilot study. The results showed that the Content Validity Index (1-CVI) for TSP 2-M ranged from .88-1.0, while S-CVI/Ave was .99 and S-CVI/UA was equal to .89. The reliability of TSP 2-M was good with the Cronbach a coefficient .92. The Cronbach a coefficients for each section and quadrant of the TSP 2-M ranged between .66 and.87. Based on the results, this study provided preliminary support for the validity and reliability of the TSP 2-M in Malaysia.